Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1582-4934.2008.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of bone formation in ectopically pre‐fabricated, autologous cell‐based engineered bone flaps in rabbits

Abstract: Biological substitutes for autologous bone flaps could be generated by combining flap pre-fabrication and bone tissue engineering concepts. Here, we investigated the pattern of neotissue formation within large pre-fabricated engineered bone flaps in rabbits. Bone marrow stromal cells from 12 New Zealand White rabbits were expanded and uniformly seeded in porous hydroxyapatite scaffolds (tapered cylinders, 10–20 mm diameter, 30 mm height) using a perfusion bioreactor. Autologous cell-scaffold constructs were wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 45 publications
(50 reference statements)
1
34
0
Order By: Relevance
“…The issue should be investigated in models addressing the kinetics of blood vessel formation within grafts (i.e., skin-fold chamber model 30 ), as well as using larger constructs, where rapid and efficient vascularization is crucial to reduce formation of a necrotic core. 31 Despite the discussed limitations, PL appears to be a promising serum substitute for the short-term 2D expansion of SVF cells and for their culture in 3D perfusion systems. As concerning the potential amount of expanded cells available using PL for therapeutic purposes, it has to be considered that adipose biopsies of 200 mL to 1 L could be obtained from a donor for clinical application without significant related morbidity.…”
Section: =Cd31mentioning
confidence: 99%
“…The issue should be investigated in models addressing the kinetics of blood vessel formation within grafts (i.e., skin-fold chamber model 30 ), as well as using larger constructs, where rapid and efficient vascularization is crucial to reduce formation of a necrotic core. 31 Despite the discussed limitations, PL appears to be a promising serum substitute for the short-term 2D expansion of SVF cells and for their culture in 3D perfusion systems. As concerning the potential amount of expanded cells available using PL for therapeutic purposes, it has to be considered that adipose biopsies of 200 mL to 1 L could be obtained from a donor for clinical application without significant related morbidity.…”
Section: =Cd31mentioning
confidence: 99%
“…[19] The challenge following the development of microcirculation in the engineered construct is to connect it to the hosts' systemic circulation, a phenomenon designated as inosculation or anastomose. [20] Inosculation between the host's and construct's vasculature is not an immediate process and may take up to eight days; this may lead to ischemia and a hostile environment. [21] Consequently, the spontaneous post-implantation neovascularization from the host is not sufficient to assure implant integration.…”
mentioning
confidence: 99%
“…However, the process of angiogenesis is an inherently slow process (estimates range from 100 mm to 1 mm per day (Mikos et al, 1993;Orr et al, 2003)), and the timely generation of a stable vascular network has long been identified as a fundamental challenge for tissue engineering (Koike et al, 2004). Because of the inherent constraints of vascular ingrowth, constructs of clinically relevant size may progressively become devoid of oxygen and nutrients in their centre upon implantation, which will be detrimental for cellular function and survival (Radisic et al, 2006;Scheufler et al, 2008). For this reason, a major research focus lies on either increasing the availability of oxygen or reducing its need in large tissue engineering constructs.…”
Section: Hypoxia In Bone Tissue Engineeringmentioning
confidence: 99%
“…Indeed, studies in cardiac tissues have shown that tissueengineered constructs of clinically relevant size are devoid of oxygen in the centre, causing massive loss of cell viability and regenerative capacity (Radisic et al, 2006). Analogous herewith, necrotic cells are observed in the centre of implanted large bone constructs (Scheufler et al, 2008). On the other hand, bone cells have the capacity to withstand the temporary hypoxia that occurs during certain stages of bone development or uncomplicated fracture repair (Drager et al, 2015) by activating the hypoxia signalling pathway.…”
Section: Introductionmentioning
confidence: 97%